Improving access to health services for female entertainment workers in Cambodia: findings from the Mobile Link randomised controlled trial. Issue 1 (March 2021) - Brody, Carinne; Chhoun, Pheak; Sovannary, Tuot; Fehrenbacher, Anne E; Moran, Alexander; Swendeman, Dallas; Yi, Siyan
Abstract: Background: Female entertainment workers (FEWs) in Cambodia who work at karaoke bars, massage parlours, and beer gardens have higher rates of HIV and sexually transmitted infections (STIs), psychological distress, substance use, and gender-based violence than the general population. Reaching these workers with health education and services has been difficult because of their hidden and stigmatised status. This study evaluates the Mobile Link intervention, which aims to engage FEWs in Cambodia by connecting them to existing services for HIV, sexual and reproductive health, and gender-based violence using short message services and voice messages to ultimately improve their health. Methods: The Mobile Link intervention consisted of text or voice messages on ten health topics, which were delivered twice a week for 10 weeks and the message topics were repeated every 10 weeks for 30 weeks (time 2) and 60 weeks (time 3). The messages were co-developed with FEWs over a 6-month period before the trial began. We used a stratified random sampling method to select 600 FEWs from a list of 4000 by age group (18–24 years old and 25–30 years old) and study sites (two sites in Phnom Penh and one site each in Battambang, Banteay Meanchey, and Siem Reap). Participants were randomly allocated to the intervention or standard-care control group. Primary outcome measures were self-reported HIV and STI testing, condom use, and contraceptive use. Secondary outcomes included contact with outreach workers, use of escorted referral services, forced drinking and gender-based violence. Intervention effects were modelled using repeated-measures multilevel mixed-effects logistic regression. Findings: Between March, 2018, and June, 2019, we included 218 women in the intervention group and 170 in the control group in the per protocol analyses after removing dropouts. There were no differences between intervention and control groups over time for primary outcomes in fully adjusted models. However, evidence of positive intervention effects was noted for some secondary outcomes: contacting an outreach worker (group by time 2 adjusted OR: 3·288 [95% CI 1·277–8·469]), receiving an escorted referral (group by time 2, 2·861 [1·089–7·518]; group by time 3, 8·150 [1·650–40·250]), and never being forced to drink at work (group by time 3, 3·945 [1·622–9·597]). Interpretation: The Mobile Link intervention effectively connected female entertainment workers in Cambodia with outreach workers and escorted referrals and reduced rates of forced drinking at work. Longer-term messaging has the potential to increase access to services and could improve health outcomes for female entertainment workers. Funding: 5% Initiative through Expertise France (Grant No. 16SANIN210).